Filter Design for Satellite Communications : Helical Resonator Technology. - Doumanis, Efstratios (Artech House space technology and applications library., 2015)
This new book primarily addresses the needs of practicing RF and microwave engineers engaged with the design of distributed filters for telecommunication and sensing applications, with particular emphasis on the space sector. This is a contemporary and comprehensive approach to the design of microwave filters with helical resonators. The very detailed step-by-step approach used throughout the book allows you to quickly familiarize with the basic concepts of microwave filter design and confidently engage with the design of helical resonator filters. In particular, several examples that present the design of filters for a wide frequency and applications range would provide a very useful tool at hand for the filter designer. Presenting you with cutting-edge design guidance, this is a complete reference for helical filter design.